A Process Model for Conformance of Health Information Systems: Towards National Interoperability - Chetty, D; Botha, A; Govender, K. K (International Journal of Business, Economics and Management, 2020)
In response to the critical challenge of lack of interoperability amongst health information systems in South Africa, as highlighted by the National eHealth Strategy, the National Department of Health (NDoH) published the Health Normative Standards Framework (HNSF) for eHealth interoperability in 2014. The HNSF stipulated that all health information systems deployed in South Africa should conform fully to all applicable standards. The CSIR as a strategic partner to the NDoH, is developing a variety of health information systems that are deployed in public sector clinics and hospitals which need to be subjected to conformance tests. This research therefore aims to develop a process model that could consistently be used to test conformance of the various health information systems to the standards and profiles prescribed by the HNSF. The Goodhue Task-Technology Fit framework was adapted as the theoretical framework, since it holds that the probability of the process model having a positive impact on performance is increased, if the characteristics of the process model match the tasks that need to be performed. The Design Science Research (DSR) methodology and Action Design Research (ADR) process were used, since they operationalised the research towards a process model, to guide the process of testing eHealth systems for conformance to the standards prescribed in the HNSF. An important outcome of the research was that the ADR process was adopted for conformance testing at the CSIR and it will periodically be adapted as required to ensure its continued relevance and fit to the environment.